Postnatal exposure to a glyphosate-based herbicide modifies mammary gland growth and development in Wistar male rats - Altamirano, Gabriela Anahí (2018)
Our aim was to evaluate whether postnatal exposure to a glyphosate-based herbicide (GBH) modifies mammary gland development in pre- and post-pubertal male rats. From postnatal day 1 (PND1) to PND7, male rats were injected subcutaneously every 48 h with either saline solution (vehicle) or 2 mg GBH/kg·bw. On PND21 and PND60, mammary gland and blood samples were collected. Estradiol (E2) and testosterone (T) serum levels, mammary gland histology, collagen fiber organization, mast cell infiltration, proliferation index, and estrogen (ESR1) and androgen receptor (AR) expression levels were evaluated. At PND21, GBH-exposed male rats exhibited greater development of the mammary gland with increased stromal collagen organization and terminal end buds (TEBs) compared to control rats. At PND60, the number of TEBs remained high and was accompanied by an increase in mast cell infiltration, proliferation and ESR1 expression in GBH-exposed male rats. In contrast, no effects were observed in E2 and T serum levels and AR expression in both days studied. Our results showed that a postnatal subacute treatment with GBH induces endocrine-disrupting effects in the male mammary gland in vivo, altering its normal development.